1986
DOI: 10.1073/pnas.83.10.3091
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequence analysis of cDNA species coding for the two subunits of inhibin from bovine follicular fluid.

Abstract: The primary amino acid structures of the 43-kDa (A) and 15-kDa (B) subunits of the 58-kDa form of the hormone inhibin have been elucidated by cloning and analysis of cDNA species derived from bovine granulosa cell mRNA.The A subunit (Mr = 32,298) is a protein of 300 amino acids with two potential N-glycosylation sites and two potential proteolytic processing sites and'has a pre-pro region of 60 amino acids. The mature B sublinit (Mr = 12,977) is a protein of 116 amino acids synthesized from a separate mRNA. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
69
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(72 citation statements)
references
References 27 publications
3
69
0
Order By: Relevance
“…The sequence of part of this fragment was similar to that described by Forage et al (1986) for a bovine…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…The sequence of part of this fragment was similar to that described by Forage et al (1986) for a bovine…”
Section: Resultsmentioning
confidence: 64%
“…The nucleotide sequence determined for a 907-bp PstI bovine genomic a-inhibin fragment contained within the XhoI fragment, that was identified by comparison of data from restriction mapping and sequence information with the complete bovine cDNA sequence reported by Forage et al (1986), is shown in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, isolation and characterization of inhibins was made possible with the development of an improved bioassay based on measurement of FSH production by rat pituitary cells in vitro [13][14][15][16]. Subsequent breakthroughs in the molecular biology and its applications, cloning of the gene encoding inhibin was made possible following characterization and purification from the bovine follicular fluid [17][18][19]. Following, large scale productions of recombinant DNA-derived inhibin, great strides were made in elucidating its role and other functions [20].…”
mentioning
confidence: 99%
“…The sequence of inhibin in several species have been elucidated by many investigators (Mason et al 1985(Mason et al , 1986Forage et al 1986) and there are 3 subunits (alpha, beta-A, beta-B) (Mason et al 1985). Inhibin is a combination of alpha either with beta-A (inhibin A) or beta-B (inhibin B) which acts as a FSH suppressor.…”
mentioning
confidence: 99%